Environmental risk determination algorithm for veterinary medicinal products - Viviana Ciuca; Viorel V. Safta; Romeo T. Cristina (Medicamentul Veterinar)
The environmental risk analysis for veterinary medicinal products is an assessment of their possible evolution, exposures and effects and is structured according to the EMEA/CVMP/ERA/418282/2005-Rev1[1], VICH GL6 (Phase I) and GL38 (Phase II) guides. The three primary components of a quantitative risk assessment are: exposure assessment, effects assessment, and risk characterization. Based on the indication of use of the veterinary medicinal product, the exposure assessment begins with the release of the active substance into the environment, and while taking into account the drug's fate and distribution, develops a predicted environmental concentration (PEC). The effects assessment begins with toxicity data and applies an assessment factor (AF) to it resulting in a predicted no effect concentration (PNEC). The risk characterization includes development of a risk quotient (RQ) that is calculated by dividing the PEC by the PNEC. If RQ ≥1 assessment moves to next tier. The paper presents an algorithm for calculating the initial risk for soil, groundwater, surface water and sediment under the action of the active ingredient in the analyzed veterinary medicinal product. Based on this calculation algorithm, a specialized interactive software has been developed to allow rapid and convenient determination of environmental risk for veterinary medicinal products. It is a very useful tool for environmental risk assessment specialists.